2023
DOI: 10.5339/jemtac.2023.2
|View full text |Cite
|
Sign up to set email alerts
|

Investigating RTS, TRISS, GCS, and FOUR as measures for predicting the mortality in trauma patients: A prospective study

Abstract: Background: Some measures have been proposed for the prediction of death after trauma; however, there is a lack of studies on this issue in trauma patients. Therefore, this study was conducted to compare the validity of four scales in predicting the death of trauma patients, and we hypothesized that the accuracies of various scales are different. Methods: This descriptive-analytical study was conducted prospectively on 600 trauma patients admitted at the emergency ward of Imam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
1
1
Order By: Relevance
“…Raygani et al's trauma prognosis research determined a GCS cut-off of 8.69, with low sensitivity (50.8%), high specificity (92.8%), and a sensitivity of 88.7%. [22] Our study's sensitivity (99.0%) and specificity (86.5%) at a GCS cut-off of 9.5 were comparable but higher than Raygani's study, suggesting that the GCS is a reliable diagnostic indicator for mortality. Variations in regional demographics and trauma profiles may explain these slight deviations.…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…Raygani et al's trauma prognosis research determined a GCS cut-off of 8.69, with low sensitivity (50.8%), high specificity (92.8%), and a sensitivity of 88.7%. [22] Our study's sensitivity (99.0%) and specificity (86.5%) at a GCS cut-off of 9.5 were comparable but higher than Raygani's study, suggesting that the GCS is a reliable diagnostic indicator for mortality. Variations in regional demographics and trauma profiles may explain these slight deviations.…”
Section: Discussioncontrasting
confidence: 54%
“…It was 7.63 (SD=0.61) for surviving patients and 4.23 (SD=1.23) for deceased patients. [ 22 ] Okasha et al reported a mean RTS of 5.37 for surviving and 3.94 for deceased patients, respectively. [ 26 ] In a study by Hadisaputra et al conducted in Bali, the mean RTS was 6.86 (SD=1.49), 4.56±1.63 for non-survivors, and 7.48±0.57 for survivors.…”
Section: Discussionmentioning
confidence: 99%